Directing dimensionality in uranyl malate and copper uranyl malate compounds. (16th August 2016) - Cole, Erica; Flores, Erin; Basile, Madeline; Jayasinghe, Ashini; de Groot, Joshua; Unruh, Daniel K.; Forbes, Tori Z.
Graphical abstract: Five uranyl malate compounds were synthesized and characterized by single-crystal X-ray diffraction, TGA, and Raman Spectroscopy. The presence of Cu(II) in uranyl hybrid materials contributes to increasing the dimensionality of the material. Abstract: Uranyl hybrid compounds are complex materials due to variability in coordination geometry, flexibility in ligand chelation, and metal hydrolysis, which leads to difficulty in controlling the secondary building units. The presence of transition metals in uranyl hybrid materials adds to the complexity, but also leads to an increase in the dimensionality of the topology from infinite chains and 2-D sheets, to 3-D framework lattices. In this study, five uranyl malate compounds were synthesized at room temperature: ((C4 H12 N2 )[(UO2 )2 (C4 H3 O5 )2 ]·4H2 O (UMal1 ), (C4 H12 N2 )[(UO2 )2 (C4 H3 O5 )2 ] (UMal1-b ), [(UO2 )(C4 H3 O5 )Cu(C10 H8 N2 )Cl(H2 O)]·2H2 O (UCuMal1 ), [(UO2 )2 (C4 H3 O5 )2 Cu(C5 H5 N)2 (H2 O)2 ]·2H2 O (UCuMal2 ), [(UO2 )2 (C4 H3 O5 )2 Cu(C5 H5 N)2 (H2 O)2 ]·2H2 O (UCuMal3 )). These compounds were characterized using single-crystal X-ray diffraction, thermogravimetric analysis and Raman spectroscopy. All five compounds contain an identical uranyl malate secondary building unit that could be further linked through the Cu(II) cation. In this system, the identity of the ligands bonded to the Cu(II) cation impacted dimensionality and could be the key to designing materials with a known uranyl building unit.